Differential release and phagocytosis of tegument glycoconjugates in neurocysticercosis: implications for immune evasion strategies. - Jorge I Alvarez; Jennifer Rivera; Judy M Teale (Public Library of Science (PLoS), 2008)
Neurocysticercosis (NCC) is an infection of the central nervous system (CNS) by the metacestode of the helminth Taenia solium. The severity of the symptoms is associated with the intensity of the immune response. First, there is a long asymptomatic period where host immunity seems incapable of resolving the infection, followed by a chronic hypersensitivity reaction. Since little is known about the initial response to this infection, a murine model using the cestode Mesocestoides corti (syn. Mesocestoides vogae) was employed to analyze morphological changes in the parasite early in the infection. It was found that M. corti material is released from the tegument making close contact with the nervous tissue. These results were confirmed by infecting murine CNS with ex vivo-labeled parasites. Because more than 95% of NCC patients exhibit humoral responses against carbohydrate-based antigens, and the tegument is known to be rich in glycoconjugates (GCs), the expression of these types of molecules was analyzed in human, porcine, and murine NCC specimens. To determine the GCs present in the tegument, fluorochrome-labeled hydrazides as well as fluorochrome-labeled lectins with specificity to different carbohydrates were used. All the lectins utilized labeled the tegument. GCs bound by isolectinB4 were shed in the first days of infection and not resynthesized by the parasite, whereas GCs bound by wheat germ agglutinin and concavalinA were continuously released throughout the infectious process. GCs bound by these three lectins were taken up by host cells. Peanut lectin-binding GCs, in contrast, remained on the parasite and were not detected in host cells. The parasitic origin of the lectin-binding GCs found in host cells was confirmed using antibodies against T. solium and M. corti. We propose that both the rapid and persistent release of tegumental GCs plays a key role in the well-known immunomodulatory effects of helminths, including immune evasion and life-long inflammatory sequelae seen in many NCC patients.